Fiqhul Wadih-Based Learning Innovation to Improve Madrasah Students' Understanding of Fiqh Content: A Qualitative Case Study at MI Riyadlus Sholihin - Zaenol Fajri; Lukmanul Hakim Efendi (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: Fiqh instruction in Islamic schools (madrasah) continues to face several difficulties, chief among them students' inadequate understanding of the ideas and rituals of worship due to traditional, memorization-focused teaching methods. The purpose of this study is to describe how students at the Riyadlus Sholihin Elementary Madrasah have improved their comprehension of the fiqh subject through innovative learning based on the Fiqhul Wadih book. Methodology: This study included a case study and a qualitative methodology. Key informants, including the madrasah principal, curriculum administrators, teachers, and students, were observed, interviewed in depth, and documented. Data reduction, data display, and conclusion drafting were the methods used for data analysis. Triangulating sources and methods enabled testing their validity. Main Findings: The findings demonstrated that applying learning based on Fiqhul Wadih greatly enhanced students' comprehension in both cognitive and worship-related domains. Students showed enhanced reasoning regarding fiqh concepts, practiced proper ablution and prayer techniques, and were better able to explain fiqh principles methodically. Additionally, through conversations, Q&A sessions, and practical experience, this learning increased student engagement and active participation. The conversation demonstrates how the book's methodical, communicative qualities, which are reinforced by interactive teaching strategies, contributed to its success. Novelty/Originality of this study: The study's findings support the effectiveness of Fiqhul Wadih-based instruction in raising students' knowledge of Islamic law. In terms of curriculum development, teacher learning methodologies, and raising the standard of Islamic education in madrasas, this research offers an alternate paradigm for learning Islamic law.